2012
DOI: 10.1155/2012/931597
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Balance in Preterm Infants during the First Week of Life

Abstract: Objective. To describe the chloride balance in infants born 25–32-week gestation, analyze the association of chloride changes with hydroelectrolytic status and their relationship with perinatal conditions, morbidities, and neurological outcome. Methods. For 7 days after birth, sodium and chloride balance, plasma potassium, phosphate, and total carbon dioxide (tCO2) were prospectively determined and strong ion difference (SID) calculated. Three multivariate regression analyses were performed to identify factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Iacobelli et al (13,33) have shown that amino acid intake, energy intake, and extremely low gestational age are all factors influencing potassium balance. The potassium balance is positive (94% of cases) when daily amino acid intake is >2 g Á kg À1 Á day À1 and negative (92%) when amino acid intake is low (<1.5 g Á kg À1 Á day À1 ).…”
Section: Impact Of New Guidelines On Potassium Balancementioning
confidence: 99%
“…Iacobelli et al (13,33) have shown that amino acid intake, energy intake, and extremely low gestational age are all factors influencing potassium balance. The potassium balance is positive (94% of cases) when daily amino acid intake is >2 g Á kg À1 Á day À1 and negative (92%) when amino acid intake is low (<1.5 g Á kg À1 Á day À1 ).…”
Section: Impact Of New Guidelines On Potassium Balancementioning
confidence: 99%
“…Interesting also, in Group 2 and 3 the rise of nutrient intakes promotes acidosis despite the optimization of sodium and chloride inputs performed in our unit. Indeed, the augmentation of differential Na + /Cl - intake observed in groups 2 and 3 should play a protective role against acidosis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sodium and chloride inputs were also recorded, and the differential Na + –Cl - mean intake was calculated as this is known to influence metabolic acid-basic abnormalities [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Reference intervals for chloride are not well defined in preterm infants. We used the ±2 SD intervals from Iacobelli et al ( 16 ), providing a range of 100 to 120 mmol/L during the first week of life.…”
Section: Methodsmentioning
confidence: 99%